Influência de estrógenos e progestinas sobre a atividade da superóxido dismutase e o estatus oxidativo em mulheres - Unfer, Taís Cristina (2013)
The deficit of estrogen that accompanies menopause may be involved in the metabolic changes and increased oxidative stress during non-reproductive female life. Hormone replacement therapy (HRT) has been used to attenuate the menopausal symptoms. It is prescribed either as the replacement of estrogen alone or the combination of estrogen with progestins. Superoxide dismutase (SOD) is a key enzyme in the control of reactive oxygen species levels and SOD modulators may have potential use as therapeutic agents in oxidative stress-associated disorders. The objectives of this study were to evaluate: i) the effects of natural and synthetic estrogens and progestins on the activity of SOD from human blood in vitro; and ii) the effect of the hormone therapy with estrogen or estrogen plus progestin on the markers of oxidative stress in the blood of postmenopausal women and the relationship among these markers and the serum levels of estradiol and progesterone. The in vitro effect of steroid hormones (17 β-estradiol 17-acetate, progesterone, β-estradiol 3-benzoate and medroxyprogesterone 17-acetate) was evaluated in the enzyme purified from human erythrocytes (CuZnSOD) (Sigma) and in samples of erythrocytes (cytosolic CuZnSOD) and platelets-rich plasma (PRP) (MnSOD and cytosolic and extracellular CuZnSOD) obtained from healthy men and women. Hormones caused a dose-dependent stimulation of erythrocyte CuZnSOD activity at low concentrations (physiological), but this effect was abolished at higher concentrations. The combination of an estrogen with a progestin had a synergic effect on the erythrocyte CuZnSOD activity. In the PRP the activity of MnSOD was not affected by hormones, whereas the CuZnSOD activity was modulated only by the natural, but not by the synthetic hormone derivatives. Four groups of women were selected to evaluate blood markers of oxidative stress: premenopausal women (n=24), postmenopausal women without hormone therapy (HT) (n=31), postmenopausal women with estrogen-only HT (ET) (n=12) and estrogen plus progestin HT (EPT) (n=16). The levels of protein carbonyl, lipid peroxidation and the activity of catalase and glutathione peroxidase did not differ among groups. However, the activities of SOD isoforms (CuZn and MnSOD) and total plasma antioxidant power (FRAP) were significantly higher in postmenopausal women under EPT compared with postmenopausal women without HT, whereas ET increased only the activity of CuZnSOD in postmenopausal women. The duration of HT and serum E2 levels were positively correlated with the activity of CuZnSOD and the total antioxidant power of plasma (FRAP levels), whereas progesterone levels were positively correlated with the activity of CuZnSOD and negatively correlated with protein carbonyl levels. The total antioxidant power of plasma was positively correlated to the CuZnSOD activity and to the GPx activity. The present study demonstrated for the first time, that the natural and synthetic steroid hormones have a direct biphasic effect on CuZnSOD activity of human erythrocytes in vitro. We also observed that the hormone replacement therapy increase the antioxidant status of postmenopausal women due to an increase of the enzymatic antioxidant defenses and this effect is more remarkable with the combined hormone therapy (estrogen plus progestin).